Genetic diversity of toxigenic Fusarium verticillioides associated with maize grains, India - Navale, Vishwambar D.; Sawant, Amol M.; Vamkudoth, Koteswara Rao (Genetics and Molecular Biology, 2023)
In the present investigation, prevalence, genetic diversity, and mycotoxin producing potential of Fusarium species associated with maize grain samples were studied from different geographical regions of India. The highest prevalence of Fusarium verticillioides was recorded as 88.52%, followed by F. coffeatum, F. foetens, and F. euwallaceae, 6.55%, 3.27%, and 1.63%, respectively. We isolated 54 strains of F. verticillioides, and their genetic diversity was studied by inter simple sequence repeats (ISSR). The ISSR fingerprints (AG) 8C and (AG) 8G showed 252 and 368 microsatellite sites in the genome of F. verticillioides and resulted in 99-100% repeatability and reproducibility. The Simpson (SID) and Shannon (H) indices (0.78 and 2.36) suggest that F. verticillioides strains exhibit moderate to high diversity. Molecular detection of fumonisin B1 (FB1) biosynthetic genes (FUM1 and FUM13) involved in FB1 production in F. verticillioides was confirmed by polymerase chain reaction (PCR). Furthermore, 91% of the strains were positive for FB1 production, which was affirmed by liquid chromatography with tandem mass spectrometry (LC-MS-MS). In-vitro appurtenance of F. verticillioides spores exhibited a high to moderate effect on the growth and development of the maize. The current finding demonstrated that most F. verticillioides strains showed a wide range of genetic diversity with varied toxigenic and pathogenic potentials. In conclusion, for the first time, F. coffeatum, F. foetens, and F. euwallaceae species were reported from maize grain samples in India. They were positive for FB1 and negatively affecting grain quality, which is a major concern in food safety.
Keywords: diversity; Food safety; Fusarium verticillioides; Mycotoxin; pathogenicity

Genome sequencing and analysis of penicillin V producing Penicillium rubens strain BIONCL P45 isolated from India - Sawant, Amol M.; Navale, Vishwambar D.; Vamkudoth, Koteswara Rao (International Microbiology, 2024)
Background A filamentous fungus Penicillium rubens is widely recognized for producing industrially important antibiotic, penicillin at industrial scale. Objective To better comprehend, the genetic blueprint of the wild-type P. rubens was isolated from India to identify the genetic/biosynthetic pathways for phenoxymethylpenicillin (penicillin V, PenV) and other secondary metabolites. Method Genomic DNA (gDNA) was isolated, and library was prepared as per Illumina platform. Whole genome sequencing (WGS) was performed according to Illumina NovoSeq platform. Further, SOAPdenovo was used to assemble the short reads validated by Bowtie-2 and SAMtools packages. Glimmer and GeneMark were used to dig out total genes in genome. Functional annotation of predicted proteins was performed by NCBI non-redundant (NR), UniProt, Kyoto Encyclopedia of Genes and Genomes (KEGG), and Gene Ontology (GO) databases. Moreover, secretome analysis was performed by SignalP 4.1 and TargetP v1.1 and carbohydrate-active enzymes (CAZymes) and protease families by CAZy database. Comparative genome analysis was performed by Mauve 2.4.0. software to find genomic correlation between P. rubens BIONCL P45 and Penicillium chrysogenum Wisconsin 54-1255; also phylogeny was prepared with known penicillin producing strains by ParSNP tool. Results Penicillium rubens BIONCL P45 strain was isolated from India and is producing excess PenV. The 31.09 Mb genome was assembled with 95.6% coverage of the reference genome P. chrysogenum Wis 54-1255 with 10687 protein coding genes, 3502 genes had homologs in NR, UniProt, KEGG, and GO databases. Additionally, 358 CAZymes and 911 transporter coding genes were found in genome. Genome contains complete pathways for penicillin, homogentisate pathway of phenyl acetic acid (PAA) catabolism, Andrastin A, Sorbicillin, Roquefortine C, and Meleagrin. Comparative genome analysis of BIONCL P45 and Wis 54-1255 revealed 99.89% coverage with 2952 common KEGG orthologous protein-coding genes. Phylogenetic analysis revealed that BIONCL P45 was clustered with Fleming's original isolate P. rubens IMI 15378. Conclusion This genome can be a helpful resource for further research in developing fermentation processes and strain engineering approaches for high titer penicillin production.
Keywords: comparative genomics; Illumina NovoSeq; Penicillin biosynthesis; Penicillium rubens; Secondary metabolites; whole genome sequencing